E-commerce issues in retail industry / Baderisang Mohamed, Mohd Sukor Md Yusoff and Nurul Ain Syauqina Azlan - Mohamed, Baderisang; Md. Yusoff, Mohd. Sukor; Azlan, Nurul Ain Syauqina (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
With the introduction of e-commerce, or internet commerce, shopping, formerly limited to brick-and-mortar companies, has taken on a new meaning. E-commerce advancements are critical in defining the retail industry's future. E-commerce has had a profound effect on retail, encouraging merchants to offer a similarly compelling purchasing experience. The best e-commerce practices have infiltrated the retail industry, and most firms already have an online presence or will soon have one. Retailers are taking advantage of modern technology that enables shoppers to examine promoted items from any location and at any time. This contributes to the growth of website traffic and revenues.